2008
DOI: 10.1016/j.disc.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Paired bondage in trees

Abstract: Let G = (V, E) be a graph with δ(G) ≥ 1. A set D ⊆ V is a paired dominating set if D is dominating, and the induced subgraph D contains a perfect matching. The paired domination number of G, denoted by γ p (G), is the minimum cardinality of a paired dominating set of G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…However the first result on bondage numbers is obtained by Bauer et al [1]. There are many research articles on the bondage number for undirected graphs and digraphs (see, for example [1]∼ [2], [5][17], [19,20], [22][28], [31]). In particular, Hu and Xu [13] have showed that the problem determining bondage number for general graphs is NP-hard.…”
Section: A Nonempty Subset B ⊆ E(g) Is Said a Bondage Set Of G If γ(Gmentioning
confidence: 98%
“…However the first result on bondage numbers is obtained by Bauer et al [1]. There are many research articles on the bondage number for undirected graphs and digraphs (see, for example [1]∼ [2], [5][17], [19,20], [22][28], [31]). In particular, Hu and Xu [13] have showed that the problem determining bondage number for general graphs is NP-hard.…”
Section: A Nonempty Subset B ⊆ E(g) Is Said a Bondage Set Of G If γ(Gmentioning
confidence: 98%
“…A constructive characterization of trees with ( ) = 2 is given by Hartnell and Rall in [12]. Raczek [73] provided a constructive characterization of trees with ( ) = 0. In order to state the characterization, we define a labeling and three simple operations on a tree .…”
Section: Corollary 122 the Bondage Number And The Paired Bondage Nummentioning
confidence: 99%
“…Raczek [73] obtained the following characterization of all trees with ( ) = 0. The concept of restrained domination was introduced by Telle and Proskurowski [74] in 1997, albeit indirectly, as a vertex partitioning problem.…”
Section: Corollary 122 the Bondage Number And The Paired Bondage Nummentioning
confidence: 99%
“…The concept of bondage in graphs was introduced by Bauer, Harary, Nieminen and Suffel in [1], and has been further studied for example in [4,6,8,10,11,13,18,21]. This concept has been considered for several domination parameters, and for a survey of results and recent developments on bondage we refer the reader to [22].…”
Section: Introductionmentioning
confidence: 99%